Pertumbuhan 11 Aksesi Stroberi yang Dibudidayakan Secara Hidroponik - Slamet Susanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
The objective of the experiment was to study the growth and fruit quality of several accessions of strawberry grown by hydroponics. The experiment was conducted at farmer farm in Pacet Cianjur, from March 1999 to June 2000. These accessions were collected from Cipanas Cianjur, Ciwidey and Pangalengan Bandung, all of those were unidentified its origin. Nutrition compound used was made by modify nutrition compound for tomato which was obtained from previous experiment. The result of this experiment showed that strawberry plant could produce runner with average one runner per month, whenever all fruit thinned. A strawberry plant produced one leave average per two week\', J 1-18 fruit per year with 13-24 gram per fruit or 210-314 gram per plant per year. It has been found that five accessions tasteless, four accessions had strong sour taste, one accession (No.4) with sweet taste and one another accession (No. 10) with sour sweet taste. The last two accessions had a good taste with fruit weight around 17 gram in average per fruit, smoth texture and adequate firmness. These accessions are being propagated for further experiment. Key words: Accessions, Hydroponics, Strawberry